Changes in sea ice cover and ice sheet extent at the Yermak Plateau during the last 160 ka – Reconstructions from biomarker records. (15th February 2018) - Kremer, A.; Stein, R.; Fahl, K.; Ji, Z.; Yang, Z.; Wiers, S.; Matthiessen, J.; Forwick, M.; Löwemark, L.; O'Regan, M.; Chen, J.; Snowball, I.
Abstract: The Yermak Plateau is located north of Svalbard at the entrance to the Arctic Ocean, i.e. in an area highly sensitive to climate change. A multi proxy approach was carried out on Core PS92/039-2 to study glacial-interglacial environmental changes at the northern Barents Sea margin during the last 160 ka. The main emphasis was on the reconstruction of sea ice cover, based on the sea ice proxy IP25 and the related phytoplankton - sea ice index PIP25 . Sea ice was present most of the time but showed significant temporal variability decisively affected by movements of the Svalbard Barents Sea Ice Sheet. For the first time, we prove the occurrence of seasonal sea ice at the eastern Yermak Plateau during glacial intervals, probably steered by a major northward advance of the ice sheet and the formation of a coastal polynya in front of it. Maximum accumulation of terrigenous organic carbon, IP25 and the phytoplankton biomarkers (brassicasterol, dinosterol, HBI III) can be correlated to distinct deglaciation events. More severe, but variable sea ice cover prevailed at the Yermak Plateau during interglacials. The general proximity to the sea ice margin is further indicated by biomarker (GDGT) - based sea surface temperatures below 2.5 °C.